Antimicrobial properties of ZnO nanomaterials: A review. Issue 5 (1st April 2017) - Kumar,, Rajesh; Umar,, Ahmad; Kumar,, Girish; Nalwa, Hari Singh
Abstract: Waterborne diseases significantly affect the human health and are responsible for high mortality rates worldwide. Traditional methods of the treatment are now insignificant as maximum bacterial strains have developed multiple antibiotic resistance toward commonly used antibiotic drugs. Recently, ZnO nanostructures, due to their biocompatible nature, have attracted the attention of the scientific community to explore and to understand their cytotoxicity, interactions with biomolecules such as proteins, nucleic acids, fats, cell membranes, tissues, biological fluids, etc., and bio-safety for proper utilization in biomedical applications. Herein, we have reviewed the recent developments for the fabrication of ZnO nanomaterials with variable morphologies, factors influencing the growth, morphology and surface defects, and various laboratory methods to evaluate the antibacterial activities toward Gram-positive as well as Gram-negative bacterial strains. A comparative study is carried out to evaluate the mechanistic approach of ZnO nanomaterials toward Gram-positive as well as Gram-negative bacterial cells. ZnO nanomaterials can interact chemically as well as physically to exhibit antibacterial activities. Chemical interactions of the ZnO nanomaterials with bacterial cells lead to the photo-induced production of reactive oxygenated species (ROS), formation of H2 O2, and release of Zn 2+ ions. In contrast, the physical interaction can show biocidal effects through cell envelope rupturing, cellular internalization or mechanical damage. Finally, surface activation through amine functionalization of ZnO nanoparticles for better antibacterial effects and cytotoxicity of ZnO nanoparticles toward cancer cells is also reviewed. Graphical abstract: